The Role of Attitude in Language Learning as a Part of Cultures - Suriati Pasang; Ramiana Ramiana; Afina Aninnas Harbi; Amaluddin Amaluddin (Edumaspul: Jurnal Pendidikan, 2023)
The research discussed the attitude toward English language learning. This research focuses on the attitude of learners. The term attitude consists of three components; behavioral, cognitive, and emotional aspects. The research collects the data by reviewing some kinds of literature related to attitudes for language learning. The findings of research show that the attitude of learners in language learning is varied based on condition and situation. The attitude Is mostly positive in the cognitive aspect, but negative in the behavioral aspect. The learners have good perception about the importance of language learning, but they still have negative behavior while learning language processing. Another finding is that language attitude refers to emotional attitude.